Financial ratio as a predictor of corporate financial distress: evidence of Malaysia / Mohd Fariz Abu Khalid, Mohd Sharil Zainal Abidin & Mohd Kamal Yusoff - Abu Khalid, Mohd Fariz (2013)
We would like to express our sole gratitude to Allah s.w.t for bringing us the patience, the joy and the guidance throughout the program. We thank Allah; we managed to complete the dissertation within the time given. We wish to express sincere appreciation to our supervisor, Associate Professor Dr Norashikin Ismail for her guidance and assistance leading to the conclusion of this research project. Fruitful discussion with her during the developing stage on the research proposal has led us to successful completion of the project and for that we are grateful to her. Few of our friends and colleagues have been of great assistance in this research study and we gratefully thank them for their help: Dr. Noraini for her opinion upon the presentation, PM Kamel Taufiq during preparing the proposal, Dr. Effendi and Husnizam Hussin for sharing knowledge on how to develop research data and make us familiar with SPSS when we had our difficulty during final stage to extract the data.